Flanking duplications and deletions associated with P-induced male recombination in Drosophila. - Preston, C.R.; Sved, J.A.; Engels, W.R. (Genetics, 1996)
We studied P element-induced recombination in germline mitotic cells by examining the structure of the recombinant chromosomes. We found that most recombinants retain a mobile P element at the site of the recombination, usually with either a deletion or a duplication immediately adjacent to the P end at which the crossover occurred. The sizes of these deletions and duplications ranged from a few base pairs to well over 100 kb. These structures fit the "hybrid element insertion" (HEI) model of male recombination in which the two P-element copies on sister chromatids combine to form a "hybrid element" whose termini insert into a nearby position on the homologue. The data suggest that P-induced recombination can be used as an efficient means of generating flanking deletions in the vicinity of existing P elements. These deletions are easily screened using distant flanking markers, and they can be chosen to extend in a given direction depending on which reciprocal recombinant type is selected. Furthermore, the retention of a mobile P element allows one to extend the deletion or generate additional variability at the site by subsequent rounds of recombination.